2012
DOI: 10.1152/ajpendo.00398.2011
|View full text |Cite
|
Sign up to set email alerts
|

Altered REDD1, myostatin, and Akt/mTOR/FoxO/MAPK signaling in streptozotocin-induced diabetic muscle atrophy

Abstract: Hulmi JJ, Silvennoinen M, Lehti M, Kivelä R, Kainulainen H. Altered redd1, myostatin, and Akt/mTOR/FoxO/MAPK signaling in streptozotocin-induced diabetic muscle atrophy. Am J Physiol Endocrinol Metab 302: E307-E315, 2012. First published November 8, 2011 doi:10.1152/ajpendo.00398.2011.-Type 1 diabetes, if poorly controlled, leads to skeletal muscle atrophy, decreasing the quality of life. We aimed to search highly responsive genes in diabetic muscle atrophy in a common diabetes model and to further characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 53 publications
5
59
2
Order By: Relevance
“…Here, our results have established Mstn-mediated down-regulation of REDD1 and p63 levels via ROS production. However, recently, Hulmi et al reported an increase in p63 and REDD1 levels in STZ-treated mice at week 1 of STZ treatment plausibly due to higher dose of STZ (180 mg/kg) and/or the type of muscles used in the study (8). Our results indicated that the basal levels of REDD1 and p63 were higher in Mstn Ϫ/Ϫ mice probably in part due to higher levels of AMP-activated protein kinase (AMPK) in these mice (40) because AMPK was shown to stimulate REDD1 in vitro (41).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Here, our results have established Mstn-mediated down-regulation of REDD1 and p63 levels via ROS production. However, recently, Hulmi et al reported an increase in p63 and REDD1 levels in STZ-treated mice at week 1 of STZ treatment plausibly due to higher dose of STZ (180 mg/kg) and/or the type of muscles used in the study (8). Our results indicated that the basal levels of REDD1 and p63 were higher in Mstn Ϫ/Ϫ mice probably in part due to higher levels of AMP-activated protein kinase (AMPK) in these mice (40) because AMPK was shown to stimulate REDD1 in vitro (41).…”
Section: Discussionmentioning
confidence: 90%
“…Mice injected with an equal volume of sodium citrate buffer were maintained as control groups. Nonfasting body weight and random blood glucose levels were determined on the day of injection and subsequently on Day 1,2,4,5,7,8,9,11,12,13,14,15,16, and 18. Mice were fasted for 9 -10 h and body weight and fasting blood glucose was measured on Day 3, 6, 10, and 17.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gastrocnemius muscle was pulverized in liquid nitrogen and homogenized in ice-cold buffer with proper inhibitors and further treated as reported previously (25). One part of the homogenate was taken for the protein puromycin incorporation examination.…”
Section: Methodsmentioning
confidence: 99%
“…However, some other genes in the Hippo pathway, such as Taz, Mst1, and Lats2, were unchanged (unpublished data). We also reanalyzed our previous microarray data from skeletal muscle in streptozotocin-induced diabetes (25). It was found that the mRNA level of YAP is not affected significantly in diabetic muscle atrophy or in exercised muscle (microarray data are available under accession no.…”
Section: Altered Hippo Signaling and Redd1 Proteinmentioning
confidence: 99%